Isolation of a human monoclonal antibody specific for the receptor binding domain of SARS-CoV-2 using a competitive phage biopanning strategy. (30th April 2020) - Zeng, Xin; Li, Lingfang; Lin, Jing; Li, Xinlei; Liu, Bin; Kong, Yang; Zeng, Shunze; Du, Jianhua; Xiao, Huahong; Zhang, Tao; Zhang, Shelin; Liu, Jianghai
Abstract: The infection of the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused more than 200 000 deaths, but no vaccine or therapeutic monoclonal antibody is currently available. SARS-CoV-2 relies on its spike protein, in particular the receptor-binding domain (RBD), to bind human cell receptor angiotensin-converting enzyme 2 (ACE2) for viral entry, and thus targeting RBD holds the promise for preventing SARS-CoV-2 infection. In this work, a competitive biopanning strategy of a phage display antibody library was applied to screen blocking antibodies against RBD. High-affinity antibodies were enriched after the first round using a standard panning process in which RBD-His was immobilized as a bait. At the next two rounds, immobilized ACE2-Fc and free RBD-His were mixed with the enriched phage antibodies. Antibodies binding to RBD at epitopes different from ACE2-binding site were captured by the immobilized ACE2-Fc, forming a "sandwich" complex. Only antibodies competed with ACE2 can bind to the free RBD-His in the supernatant and be subsequently separated by the nickel-nitrilotriacetic acid magnetic beads. rRBD-15 from the competitive biopanning of our synthetic antibody library, Lib AB1, was produced as the full-length IgG1 format. It was proved to competitively block the binding of RBD to ACE2 and potently inhibit SARS-CoV-2 pseudovirus infection with IC50 values of 12 nM. Nevertheless, rRBD-16 from the standard biopanning can only bind to RBD in vitro, but not have the blocking or neutralization activity. Our strategy can efficiently isolate the blocking antibodies of RBD, and it would speed up the discovery of neutralizing antibodies against SARS-CoV-2.